Behold, the human being: Hans Urs von Balthasar's theology of the Paschal Triduum and the self in dementia. Issue 2 (March 2023) - James, Rob; Stevens, Becca
This article explores the theological resources within the thought of Hans Urs von Balthasar that may be of use to Christians as they consider or face the changing nature of the experience of self following a dementia diagnosis. It takes Balthasar's ideas about the dying and then dead Jesus being the gradual and then total alienation of Father from Son as a model for how dementia can alienate a person from their sense of self. This article does not offer solutions as such but finds hope in the message of Easter that humans are re-membered.